Methionyl human growth hormone in Turner's syndrome. Issue 10 (October 1988) - Rongen-Westerlaken, C; Wit, J M; Drop, S L; Otten, B J; Oostdijk, W; Waal, H A; Gons, M H; Bot, A; Van den Brande, J L
Abstract : Sixteen girls with Turner's syndrome aged 7.9-15.2 years (bone ages 7.0-11.8 years) were given methionyl growth hormone (somatrem) 4 IU/m2 body surface daily, corresponding to 0.9 IU/kg/week. During one year of treatment their mean (SD) height velocity increased from 3.4 (0.9) to 7.2 (1.7) cm/year and height prediction from 148.2 (4.4) to 150.0 (4.4) cm. All the girls except one had a height velocity increment of more than 2 cm/year and these velocities are above the age references for girls with Turner's syndrome. The girl with a low growth response had antibodies against growth hormone with high binding capacity (3.7 U/l). The height velocity increment was inversely correlated with age and bone age, but this might be partly due to the somewhat higher dosage/m2 body surface and kg body weight that the younger patients were given because of the rounding off of the dose. The better results of our study compared with those of other workers who used similar dosages but did not give the drug as often suggest that giving it daily might have increased the growth response as it does in children deficient in growth hormone.